Operating with External Arguments of Douady and Hubbard. (30th December 2007) - Pastor, G.; Romera, M.; Alvarez, G.; Nunez, J.; Arroyo, D.; Montoya, F.
Abstract : The external arguments of the external rays theory of Douady and Hubbard is a valuable tool in order to analyze the Mandelbrot set, a typical case of discrete dynamical system used to study nonlinear phenomena. We suggest here a general method for the calculation of the external arguments of external rays landing at the hyperbolic components root points of the Mandelbrot set. Likewise, we present a general method for the calculation of the external arguments of external rays landing at Misiurewicz points.